PHYSICAL THERAPY OF PATIENTS AFTER MYOCARDIAL INFARCTION - Osypchuk, R. I.; Zhyhulova, E. O.; Zaikin, A. V.; Zdaniuk, V. V. (Rehabilitation and Recreation, 2023)
The article summarizes modern recommendations for physical therapy of patients after a heart attack. The use of a complex approach of physical therapy for this problem significantly speeds up the recovery period after the disease, reduces the risk of complications. It is the complex approach that makes it possible to achieve the set goal and tasks of physical therapy as quickly as possible, at all periods of treatment, taking into account the individual characteristics of each person. Myocardial infarction is a serious and common cardiovascular disease that poses a great threat to the health and life of people around the world, including Ukraine. According to the Ministry of Health of Ukraine, in 2020, more than 160,000 cases of myocardial infarction occurred in Ukraine. This makes diseases of the cardiovascular system one of the most common and dangerous types of diseases in Ukraine. It is also worth noting that myocardial infarction in Ukraine caused more than 55,000 deaths in 2020, which makes it one of the most deadly diseases. After a myocardial infarction, it is important to take all necessary measures to restore health and prevent complications and repeated heart attacks. One of the key elements in the recovery process is physical therapy. Physical therapy after a myocardial infarction is a comprehensive approach to restoring health, the main tasks of which are to improve the functions of the heart and blood vessels, reduce the risk of repeated infarction, improve the quality of life, reduce symptoms and increase physical activity. Successful recovery after a myocardial infarction requires interaction between the patient and the medical staff. Patients should receive appropriate medical care and support from doctors, nurses and physical therapists at various stages of treatmen.